The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2196/jmir.7383
|View full text |Cite
|
Sign up to set email alerts
|

Mobile App for Treatment of Stress Urinary Incontinence: A Cost-Effectiveness Analysis

Abstract: BackgroundMobile apps can increase access to care, facilitate self-management, and improve adherence to treatment. Stress urinary incontinence (SUI) affects 10-35% of women and, currently, an app with instructions for pelvic floor muscle training (PFMT) is available as first-line treatment. A previous randomized controlled study demonstrated that the app benefitted symptom severity and quality of life (QoL); in this study we investigate the cost-effectiveness of the app.ObjectiveThe objective of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 35 publications
0
93
0
Order By: Relevance
“…Therefore, app use may be considered a noninvasive therapeutic tool for women who want to manage their routine more independently 32 . Corroborating such findings, one study 33 suggested that the use of an app to treat stress UI has a good cost‐benefit ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, app use may be considered a noninvasive therapeutic tool for women who want to manage their routine more independently 32 . Corroborating such findings, one study 33 suggested that the use of an app to treat stress UI has a good cost‐benefit ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Other countries already use mobile phones to assess and treat certain diseases [28-31]. With the widespread availability of the internet and decreasing cost of distant medical services over time, the internet health care mode has had an impact on many developing countries, where medical services and resources are concentrated in large cities.…”
Section: Discussionmentioning
confidence: 99%
“…The app, which provides a treatment program for SUI with a focus on PFMT, is referred to here as the “app-based treatment.” We demonstrated efficacy regarding symptoms, quality of life, and urinary leakage in a previous randomized controlled trial (RCT) [16]. The treatment was cost effective [17] and had persistent long-term effects [18].…”
Section: Introductionmentioning
confidence: 99%